Learning Apache Cassandra : build an efficient, scalable, fault-tolerant, and highly-available data layer into your application using Cassandra /: build an efficient, scalable, fault-tolerant, and highly-available data layer into your application using Cassandra. (2015) - Brown, Mat
No abstract available